Analysis of spectrally efficient two‐way relay assisted free space optical systems in atmospheric turbulence with path loss. (6th May 2014) - Puri, Parul; Garg, Parul; Aggarwal, Mona
Summary: In this paper, we investigate the performance of two‐way relay assisted free space optical systems over atmospheric turbulence‐induced fading channels affected by molecular absorbtion‐induced path losses. A three node, dual‐hop, bi‐directional, half‐duplex relaying system with independent but not necessarily identically distributed channels is considered. Spectral efficiency is achieved by employing network coding to complete data transmission in two‐time phases. Closed form expression for system outage performance is derived considering decode‐and‐forward protocol. Additionally, the error performance in terms of average symbol error rate for M‐ary phase shift keying is evaluated. Further, the net achievable capacity of the system is also calculated. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We investigate a network‐coded, decode‐and‐forward, two‐way relay‐assisted free space optical communication system. The relay establishes one round communication between the terminal nodes in two time phases when direct communication is not possible between the terminal nodes because of large distance or in presence of an obstruction. Closed form expressions for system outage, error performance, and achievable capacity have been presented.